Identificación de competencia de liderazgo en jóvenes dominicanos - Urbaez, Nancy (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2019)
The main goal of this research was to determine the leadership competencies for younger adults in Santo Domingo. The sample has 405 Dominican teenagers between 18 and 35 years old. Two competencies questionnaires were used: One the Emotional and Social Intelligence Competencies (ESCI) and the other Leadership Competency questionnaire (LCI). Results show these leaders can handle competencies for both instruments at middle level. For the ESCI, there was not difference among sex, age has an inverse relationship, the level of education has a direct relationship and there are differences among the type of organization. For the LCI, only age and level of education has an impact on the way the competency is handle by the leader.